From suspicion to collaboration: defining new epistemologies of reflexive practice for legal translation and interpreting - Martin Ruano, Rosario (The Journal of Specialised Translation, 2014)
Existing Codes of Ethics for translators and interpreters working in institutional settings repeatedly require their strict adherence to apparently sacrosanct values including Fidelity, Accuracy, Neutrality or Confidentiality. Existing deontology seems to mould invisible beings who are annulled or disappear to unobtrusively give a voice to other persons or texts. Nevertheless, in situations marked by conflict and asymmetry, these seemingly indisputable values prove to be not only scarcely self-explanatory but also paradoxical, and indeed are very often the source of complex ethical dilemmas for professionals who perform an essentially interventionist task. Drawing on various examples, and aided by concepts from recent critical approaches to institutional and legal translation and other related fields, this article will problematise the theoretical discourse underpinning instruments regulating legal translation practice, with emphasis on two recurrent concepts: Accuracy and Neutrality. The ultimate goal of this endeavour will be to contribute to a more nuanced understanding of the role played by institutional translators and the acute practical and ethical complexities they face.